Ce(III) and Ce(IV) (re)distribution and fractionation in a laterite profile from Madagascar: Insights from in situ XANES spectroscopy at the Ce LIII-edge. (15th March 2015) - Janots, Emilie; Bernier, Felix; Brunet, Fabrice; Muñoz, Manuel; Trcera, Nicolas; Berger, Alfons; Lanson, Martine
Abstract: The distribution of trivalent and tetravalent cerium, Ce(III) and Ce(IV) respectively, in a lateritic profile from Madagascar, has been characterized by X-ray-absorption near-edge structure (XANES) spectroscopy at the Ce LIII -edge on the LUCIA beamline (SOLEIL synchrotron, France). XANES spectra were acquired on bulk-rock samples as well as on specific lateritic minerals or polymineral zones (in-situ measurements) of the tonalite bedrock and the three overlying weathered horizons (C-, B- and A-horizons). Geochemically, the bedrock, and the A- and C-horizons show similar rare earth element content (REE = 363–405 mg/kg). They also display the same positive Ce-anomaly (CeCN /Ce ∗  = 1.12–1.45), which is therefore likely to be inherited from the bedrock. In the B-horizon, the higher REE content (REE = 2194 mg/kg) and the larger Ce-anomaly (CeCN /Ce ∗  = 4.26) are consistent with an accumulation zone caused by the evaporation of groundwater during the dry season. There is a good agreement between the Ce(III)/Cetotal ratio (XCe(III) ) deduced from the positive Ce-anomaly (bulk-rock geochemical data) and that derived from XANES spectroscopy on the same bulk-rock samples (BR-XCe(III) -XANES) in the bedrock, and the C- and B-horizons. In the A-horizon, XANES measurements on bulk rock and minerals revealed a higher BR-XCe(III) -XANES (up to 100%) compared to the XCe(III) deduced from geochemical data (XCe(III)  = 79%). The preservation of a positive Ce-anomaly in the A-horizon suggests that the Ce mobilization and redistribution during weathering occurred with no significant Ce fractionation from other trivalent REE. Remarkably, the only investigated sample where cerianite is observed belongs to the B-horizon. Within this horizon, Ce oxidation state varies depending on the microstructural position (porosity, cracks, clay-rich groundmass). The highest Ce(IV) concentrations are measured in cerianite (and aluminophosphates) localized in pores at the vicinity of Mn-rich domains (XCe(III) -XANES = 30–51%). Therefore, Ce fractionation from other REE is attributed to a Ce oxidation and precipitation potentially assisted by oxyhydroxide scavenging. In the C-horizon, Ce(III) and Ce(IV) are mainly distributed in REE-minerals of the rhabdophane group found in pores and cracks. The similarity between the Ce(III) proportion of rhabdophane grains (XCe(III) -XANES = 74–89%) with that of the bedrock (BR-XCe(III) -XANES = 79%) suggests no significant fractionation of Ce(III) and Ce(IV) between solution and mineral during the successive stages of primary REE-mineral alteration, transport in solution and secondary precipitation in the incipient stages of weathering. Overall, our novel spectroscopic approach shows that Ce is not necessarily oxidized nor fractionated from other REE during weathering in lateritic conditions. This implies that like Ce(III), Ce(IV) can be mobilized in aqueous fluids during weathering, possibly thanks to complexation with organic molecules, and can precipitate together with Ce(III) in secondary REE-bearing minerals. The corollary is that (paleo)redox reconstructions in soils and/or sediments based on Ce-anomaly in weathered rocks or minerals must be interpreted with caution.